Animal Genetics (IntechOpen, 2021)
Animal genetics is a field of science with important theoretical and practical significance in finding the answers for the actual problems of mankind. We hope that the readers will discover some new facts regarding the relationship between plasma proteins and boar semen freezability, the importance of some behavioral factors that affect reproduction in horses, and also an important chapter regarding the use of genetically modified organisms for the repopulation of species of commercial importance in aquatic environments, their effect on the genetic pool, risks to protected areas, and policies for their proper management.